Jama Masjid call of the soul - Batra, N. L. (New Delhi Niyogi Offset, 2005)
On the architecture of Jama Masjid, mosque in Delhi, India.
Keywords: Jama Masjid (Delhi, India); Jama Masjid (Delhi, India) -- Pictorial works